Investigation of Thermal Properties via Chemical Synthesis and Characterization of Nickel Oxide Nanoparticles - Oudah Mezan, Salim; Abed, Anwar Khairi; Thjeel Jabbar, Abdulkareem; Tuama, Alaa Nihad (Journal of Neonatal Surgery, 2025)
Nanoparticles of Nickel Oxide can be synthesized by the sol-gel method, which is a bottom-up approach to synthesis. Sodium hydroxide (NaOH), nickel acetate, and cetyl trimethyl ammonium bromide (CTAB) theyre all used in this experiment. The nickel hydroxide was chemically treated and then heated at 350 ͦ C to produce nickel oxide (NiO) nanoparticles. They theyre agitated continuously until the pH reached 7.5. There are many applications of nickel oxide, for example in catalysis, sensors, and so on, with its interesting and significant thermal properties. They theyre able to determine the structure and phases of the interfaces using X-Ray Diffraction (XRD), transmission electron microscopy (TEM), and X-ray photoelectron spectroscopy (XPS). Using scanning electron microscopy (SEM), the surface morphology of the sample was investigated, and NiO particle size increased with temperature. This method is simpler than other methods and costs less than other methods. In conclusion, our experiments have shown that chemically synthesizing nickel oxide nanoparticles and characterizing them microscopically can provide good results